Menentukan Pola Debit Rata Rata Tahunan - Wahyuni, Sri Eko (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
Time series analysis applied to hydrological data is generally used to forecast the in coming series of data such that use can make use of the information to manage, control, and anticipate the posible occurence of natural phenomena. This paper applied time series analysis to discharge data at Kali Kunto, Central Java. The data shows that the annual discharge at Kali Kunto tends to follow an ARMA (1,1) to ARMA (2,2). The appropriate ARMA model can be obtained through calibration stage. Keywords: time series analysis, discharge patternPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3908[How to cite: Wahyuni, S.E., 2005, Menentukan Pola Debit Rata Rata Tahunan, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 50-56]